PROPOSED MARKETING STRATEGY TO INTEGRATED MARKETING COMMUNICATION OF BANK SYARIAH MANDIRI (The Indonesian Journal of Business Administration, 2019)
The Banking Industry is the Financial Services Industry with the largest assets in Indonesia. This then makes this industry in a fierce competition. Based on its principles in Indonesia, the banking system is divided into 2 (two) forms, namely Islamic banks and conventional banks. Bank Syariah Mandiri (BSM) is a Sharia commercial bank with the largest market share in Indonesia. However, BSM as a Sharia commercial bank has not become the top choice. This can be seen from the small market share of Islamic banks in the industry.Keywords:  Sharia Bank, Marketing Mix, Marketing Strategy